The evolution of the timber sector in lowland Bolivia: examining the influence of three disparate policy approaches - Pacheco, P.; Jong, W. de; Johnson, J. (2010)
This paper assesses the influence of forest policies on forestry development, and especially timber production, in Bolivia during three different periods of time. The first period began in the early 1970s when a conservative forest policy was adopted privileging commercial logging companies, and thus fueling land conflicts in particular with indigenous people, allowing a minority to accumulate considerable wealth, and marking the onset of forest degradation. From the mid-1990s, innovative policies were implemented to promote sustainable forest management, enhance the collection of forest royalties, improve the sector access to international timber markets, and include a wide range of social actors in the forest sector. While the adopted policy led to initial improvements in forest management practices, it failed to tackle inherent institutional weaknesses and increase the economic benefits from forest use to local forest users, which stimulated informal logging expansion. A third period emerged when the Morales administration came to office in 2006, questioning the underlying principles of the previous policy reform, and adopting a discourse in favor of a more equitable income distribution. Main answers to promote better income distribution are found in the distribution of public lands, but with a lack of actions to leveling the playing field among different forest users. Ironically, these policies could strengthen the bargaining position of timber companies, and foster short-term decision making in forest use, and thus illegal logging in a context of weak state control and persistence of elite capture.